STRATEGI PENGENDALIAN BANJIR KOTA MERAUKE PROVINSI PAPUA SELATAN - Gunawan Purba, Hisar; Mujiati; Manalu, Janviter (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2025)
This research aims to examine the Flood Control Strategy of Merauke City with the approach of existing drainageconditions, vulnerability testing and spatial planning policies of Merauke City. The background of the research departsfrom the increasing frequency of extreme rainfall and the threat of tidal flooding due to climate change and thecharacteristics of coastal geomorphology that trigger higher flood risks. This research uses descriptive and quantitativeapproaches. Data sources were obtained from primary data which were the results of interviews and fieldobservations while secondary data were obtained from relevant agencies. The results showed that the flood drainagechannel was not optimal, the vulnerability indicator of Merauke city was 2.2 on a scale of 4 with a moderate category,and the impact of changes in the RDTR of Merauke city in 2023. The height of flood water in Merauke city is still low(average 0.5 - 1m) but the flood area is increasing, especially in areas with high population density and low areas dueto land changes and residential development in infiltration / low areas. Flooding in the city of Merauke is due to highrainfall and overflow of water from the drainage as a result of siltation in the drainage and damage to severalfloodgates. The strategy to control flooding in Merauke city is by optimizing flood drainage channels and buildingretention ponds, especially in coastal, densely populated and low-lying areas, as well as by spatial planning for theprotection of infiltration zones and water boundaries in changing land functions and increasing public awareness inmaintaining the cleanliness of drainage channels